Assessing Temporal and Territorial Performance of SDG 11 at Local Scale - Temerdek-Ivan, Kinga; Mezei, Vivien (Studia Universitatis Babeș-Bolyai. Geographia., 2025)
Assessing Temporal and Territorial Performance of SDG 11 at Local Scale. This study aims to evaluate the performance of each LAU (Local Administrative Unit) within Satu Mare County and the Satu Mare Metropolitan Area in achieving Sustainable Development Goal 11 (SDG 11) - “Sustainable Cities and Communities”, for two distinct reference years: 2016 and 2024. For this purpose, a dataset was collected, based on which ten relevant indicators, identical for both years analysed, were calculated. The data were organised in a PostgreSQL database, where most of the computations were performed, including the normalisation process of the indicators. The SDG 11 Index was calculated using the normalised values, applying equal weights to each indicator. This approach enabled the assessment of the progress achieved over the past eight years towards achieving SDG 11, both at the level of Satu Mare County and the metropolitan area. Keywords: SDG 11, local level, PostgreSQL, Temporal analysis, Satu Mare